Teachers’ Understanding on Their Roles in Online Learning: (A Case Study at A Senior High School in Makassar) - Hadira Hadira; Kisman Salija; Baso Jabu (Har Press Indonesia, 2021)
This research tried to investigate the teacher’s understanding on their roles, to find out problems and to reveal solutions of the problems that the teacher met during online learning. This research was qualitative research, a case study, with two teachers as subjects. The instruments used were interview and documentation. There were five aspects used to find teachers’ understanding, namely designer/ planning role, social role, cognitive role, technological domain and managerial domain. It was found out that teachers had done and understood their role in online learning. The problems were from their students, namely lack understanding of instruction from the teacher, attendance, submitting task, and feeling bored and tired with online learning. There was also problem from the teacher related to the app used. The teachers overcame the problems from students by giving repetition so the students understood, reporting the lateness of students and sending material via WhatsApp group to the students who can’t join the class, giving additional time to submit task, trying to communicate well about the problem students had and giving clear instructions. For the Zoom app, the teacher had to login again.